The Ethical and Legal Consequences of Organ Donation - Sylvana, Yana; S, Michelle Angelika; Wijaya, Hanna; Firmansyah, Yohanes; Utomo, St. Laksanto (International Journal Labs, 2022)
Background: The transfer of all or part of a donor's body organ tissue to a recipient in the hopes of improving the recipient's quality of life is known as transplantation. Meanwhile, organs are important parts of the human body that are made up of a range of tissues that can maintain structure, vascularity, and the ability to conduct physiological functions. Aim: Based on the title, this research aimed to review the ethical and legal consequences of organ donation in Indonesia. Method: This research is a multidisciplinary research, which elaborates on the health sector with the main focus of discussion in the field of law. The type of research that was used in this journal research is normative legal research. Findings: By assuring security, safety, volunteering, benefit, and fairness in organ transplant services for both donors and recipients, the Republic of Indonesia's Government Regulation No. 53 of 2021, governing the Transplantation of Organs and Body Tissues, was developed